Dust Transport in Mine Airways - R. V. Ramani; R. Bhaskar (The National Institute for Occupational Safety and Health (NIOSH), 1988)
"The National Academy of Sciences (1) recognized the importance of studying the spatial and temporal characteristics of respirable coal mine dust atmospheres. In this paper, the progress to date of a research project on dust transportation and deposition in mine airways is presented. A mathematical model is proposed for studying the transport of dust. A source representative of dust generation in underground coal mining is defined. The influence and applicability of surface roughness, dispersivities, coagulation and reentrainment to vine dust flow arc examined. A convective-diffusion model is proposed for the transport and deposition of dust in mine airways. Using the model, the spatial and temporal characteristics can be evaluated in terms of dust concentrations in the mine atmospheres.INTRODUCTIONThe prediction of the behavior of fine particles Is Important in many fields of science and engi¬neering including physics, chemistry, mining, mineral processing, and atmospheric science. In mining from the health point of view, fine coal dust is associated with the appearance of pneumoconiosis in miners exposed to the dust. Also, in addition to being a nuisance factor obscuring visibility and general mobility of miners, it can lead to sudden catastrophic incidences of explosions. This paper outlines the progress to date of a research project on dust transportation and deposition in mine airways. A mathematical model is proposed for studying the transport of dust for the various mechanisms. The dust dispersion is defined in terms of a dispersion term determined from experimental data by Skubunov (23). Coagulation is considered as one of the mechanisms that can lead to changes in the particle size distribution. Reentrainment as a possible secondary source of dust was examined during model development but was not included in the final model."